Effects of an exercise program with or without a diet on physical fitness in obese boys: a three-year follow-up - Garcia-Hermoso, Antonio; Saavedra, Jose M.; Escalante, Yolanda; Dominguez, Ana M.; Castro-Pinero, Jose (Progress in Nutrition, 2018)
Childhood obesity is a global epidemic, and understanding the relationship between physical fitness and various forms of intervention in obese children is essential to implementing effective exercise programs. The objective of the present study was to conduct a long-term follow-up (three years) of how an exercise program with or without diet affects the physical fitness components of obese boys. The participants were 18 boys, ages between 8 and 11, divided into two groups according to the program they followed. The exercise group (E group) followed a physical exercise program (three 90-minute sessions per week), and the exercise plus diet group (E+D group) this physical exercise program plus a low calorie diet. Physical fitness was assessed by the European physical fitness test battery including flamingo balance, plate tapping, sit-and-reach, handgrip strength, standing broad jump, sit-ups, bent-arm hang, 10×5-metre shuttle run, and 20-metre endurance shuttle run. Kruskal-Wallis test was applied to reveal overall intergroup differences (E and E+D group), and measurements showing significant differences were further analysed for differences between individual groups by the Mann-Whitney U-test. In both groups, changes were observed in various physical fitness parameters, especially limb speed, agility, aerobic fitness, and muscular strength in absolute and relative terms (which improved in more than one evaluation). Differences between the two programs were observed only in the short term. It was found that long-term longitudinal interventions based on exercise programs with or without diet produce improvements in obese children’s physical fitness.